Sobre o conhecimento da coisa-em-si segundo Schopenhauer - García, Roger Antonio Pérez (Voluntas: Revista Internacional de Filosofia, 2020)
This paper proposes to analyze Schopenhauer’s methodological and hermeneutical considerations regarding the knowledge of the thing-in-itself. For this purpose, I explain the nature of the philosophical abstraction in light of the primacy of the metaphysics of the Will. I argue that the possibility of the philosophical research is rooted on the interpretation of self-knowledge as an instance of the Will’s objectivation. In this regard, I will plead that the definition and criteria developed by Schopenhauer for his philosophy are established at the expense of deductive demonstration, in favor of a peculiar and particular form of abstraction fitted for the philosophical enterprise and subject matter. Finally, I will present an interpretation of the epistemological basis of reflection in line with schopenhauerian philosophy.